The social and educational dimension of the European Union sport-related policy and its influence on national policies: The case of Greece - Σακκά, Σταυρούλα (Πανεπιστήμιο Πελοποννήσου, 2017)
This thesis is an attempt to analyse the implications of the European Integration on the sport policy developments related to its social and educational dimension. In particular, the objective of this thesis is to identify how and at what level the European Union (EU) initiatives, recommended in the White Paper on Sport, are implemented at national level. The aim is to identify EU pressures, the mechanisms and the degree of domestic change, in the light of the new EU competence in sport after the ratification of the Lisbon Treaty. This will be achieved by using the concept of Europeanisation as a theoretical framework for studying the EU influence at the national level. Europeanisation is examined as a horizontal process of ‘policy learning’ applied on the policy field of sport. The point of departure for this research project is the EU developments in the field of sport policy since 1985. The research is made upon the case of Greek sport policy, where Greece is a Mediterranean country with little influence on EU affairs. This framework explores the role of the EU institutions related to sport policy-making and implementation, including an overview of the current policy rationales reflected in the agenda-setting for sport and the sport stakeholders’ involvement. Before shifting attention to the domestic impact, the framework of Greek sport policy and the main social areas of sport policy action are presented. The methodology of this case study research includes a qualitative analysis of soft-law EU instruments, EU and domestic sport-related records and in-depth interviews with sport policy-makers. These provided valuable information for the ‘Europeanisation effect’ under the period of investigation 2007-2013. With regard to the results of this study, the degree of change in the Greek sport policy due to EU pressure for convergence is average and can be characterised as ‘absorption’. Some Europeanisation is evident, arising from the provision of funding, the policy transfer through Member States’ cooperation, structured dialogue and networking and the setting of broad EU policy aims and objectives. The preferences and actions of domestic sport policy-maker remain highly significant in determining ultimate outcomes (Chapman, 2005). This is because the EU-level sport policy is still ‘indirect’ or else ‘supportive’ and national governments still maintain their sovereignty in the field of sport.
Η κοινωνική και εκπαιδευτική διάσταση της σχετικής με τον αθλητισμό πολιτικής της Ευρωπαϊκής Ένωσης και η επίδραση της στις εθνικές πολιτικές: Η περίπτωση της Ελλάδας
Keywords: Αθλητισμός - Δίκαιο και νομοθεσία - Ευρωπαϊκή Ένωση, Χώρες της; Αθλητισμός - Κοινωνικές απόψεις - Ευρωπαϊκή Ένωση, Χώρες της; Sports - Law and legislation - European Union countries; Sports - Social aspects - European Union countries; Αθλητισμός - Πολιτικές απόψεις - Ελλάδα; Sports - Political aspects - Greece; Europeanisation; Sport policy; White Paper on Sport; Greece; Εξευρωπαϊσμός; Αθλητική πολιτική; Λευκή Βίβλος για τον Αθλητισμό; Ελλάδα